The Influence of Human Resource Management, Organizational Culture, Transformational Leadership on Talent Management and Organizational Commitment of Medical Personnel in Thailand - Udomchairat, Nutchaya; Uon, Vichit; Prayurhong, Nontipan (Journal of Posthumanism, 2025)
The advancement of current medical technology is progressing in the opposite direction of the healthcare workforce capacity. It has been found that over a half of countries in the world are facing a crisis of medical personnel shortage. The purpose of this research is to analyze the influence level of factors on talent management and organizational commitment of medical personnel in Thailand. The researchers employed a mixed-method approach, using the component synthesis to obtain research variables, leading to the development of a quantitative research tool. The quantitative data were analyzed by using the IBM SPSS AMOS 24 statistical software to examine the structural equation modeling (SEM). The results revealed that Human Resource Management (HR), Organizational Culture (OC), and Transformational Leadership (TL) had an influence on Talent Management (TM) at a level of -.43, .74, .23 respectively; and these three variables had an influence on Organizational Commitment (OM) at a level of .67, .00, .24 respectively. In addition, the findings reinforce the hierarchy of needs and also the need for a good response in other areas from organization, which is a positive driver for talented people to be committed to the organization.